Peran Kepala Sekolah dalam Meningkatkan Motivasi Kerja Guru di MI Al-Hidayah Pojokrejo Kesamben Jombang - Eny Fatimatuszuhro Pahlawati; Selfania Fatmawati (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2018)
This study aims to determine the Role of School Principals in Increasing Motivation of Teacher Work at MI Al-Hidayah Pojokrejo Kesamben Jombang using a qualitative approach. This is based on concrete social reality, that the motivation of teacher work at MI Al-Hidayah Pojokrejo Kesamben Jombang cannot be separated from the role of the School Principals. In this study data collection techniques used were interviews, observation, and documentation, the extent to which the results achieved in motivating teacher work, barriers and what efforts were made to increase motivation. While the data analysis technique uses descriptive qualitative techniques, data analysis that produces detailed descriptions of the situation, events, interactions and behavior of people, in this case is the motivation of the teacher's work. The results of this study indicate that the role of School Principals in increasing the motivation of teacher work at MI Al-Hidayah Pojokrejo Kesamben Jombang includes their role as work partners, participants, supporters, giving mandates, making workplaces that are fun and as an example for teachers who can then growing work motivation on teachers at MI Al-Hidayah Pojokrejo Kesamben Jombang.